Effect of silica fume addition on the chloride related transport properties of high performance concrete (2012)
Corrosion of steel reinforcement due to chloride penetration is the major cause of durability problems in concrete. In that way, this paper summarizes the results of an experimental research carried out in order to investigate the influence of the Silica Fume (SF) content on some chloride related transport properties. To achieve this, the compressive strength, the self diffusion chloride penetration, the charge passed under a non steady chloride migration test (ASTM C1202) and the AC resistivity were measured on concrete mixes of high performance concrete. Four concrete mixes were cast incorporating 0, 5 10 and 15% of SF as addition of Ordinary Portland Cement. The results showed that the silica fume in concrete causes an increase in strength and a reduction in chloride ion permeability; however, clear differences were found between the results of long diffusion and rapid electrical tests.